Effect of electrically heated catalytic converter on emission characteristic of a motorcycle engine in cold-start conditions: CFD simulation and kinetic study. (25th December 2017) - Mianzarasvand, Fatemeh; Shirneshan, Alireza; Afrand, Masoud
Highlights: The minimum heating temperature that converter reaches to light-off point is 450 K. The heaters at the inlet of the converter is more effective than another position. Suitable conversion occurs after 30 s for catalyst with heaters in continues heating. In temporary heating, higher conversion occurs when 1000 K heater was turned on 35 s. Abstract: Emissions from motorcycles are well known to be a serious cause of environmental pollution. One of the most effective ways to reduce the emissions during cold start of the motorcycle engine is using electrically heated catalytic converters (EHC). In this study, a kinetic model has been developed by using CFD methods to investigate the effects of using EHC on CO emission from motorcycle engines. Apart from three different heating temperatures (600, 800 and 1000 K), the other studied parameters included the heating position (the inlet and the mid-section of the catalyst converter) and heating duration (20, 25 and 35 s). Results showed that using the heater at the inlet of the catalytic converter is more effective than when it is in mid-section and the converter has a higher reaction performance. Moreover, the results indicated that the minimum heating temperature which required the converter to reach the light-off point is 450 K. In addition, the results revealed that when the heaters were turned on prior to cold starting the engine for duration of 35 s, the higher CO conversion occurs.